Local Governance Quality and the Environmental Cost of Forced Migration - Cevat Giray Aksoy; Semih Tumen (Institute of Labor Economics (IZA), 2020)
Can high-quality local governance alleviate the environmental impact of large-scale refugee migration? The recent surge in refugee flows has brought additional challenges to local governments in Europe, the Middle East and certain regions of Africa and Asia. In this paper, we focus on the case of Syrian refugees in Turkey and show that the quality of local governance plays a critical role in mitigating the environmental deterioration. We employ text analysis methods to construct a unique data set on local governance quality from the independent audit reports on municipalities. Using a quasi-experimental econometric strategy, we show that the Syrian refugee influx has worsened environmental outcomes along several dimensions in Turkey. Specifically, we find that the deterioration in environmental outcomes is almost entirely driven by provinces with poor-quality governance. Those provinces fail to invest sufficiently in waste management practices and environmental services in response to increased refugee settlements. We argue that good local governance practices can smooth out the refugee integration process and complement the efforts of central governments.
Keywords: F22; H76; Q53; 330; Syrian refugees; environment; waste management; local governance; text analysis